Investigating Violence and Control Dyadically in a Help-Seeking Sample from Mozambique - Nicola Graham-Kevan; Antonio Eugenio Zacarias; Joaquim J. F. Soares (The Scientific World Journal)
A sample of 1442 women attending a Forensic Healthcare Service provided information on their own and their partners' use of controlling behaviors, partner violence, and sexual abuse, as well as their own experiences of childhood abuse. Using Johnson's typology, the relationships were categorized as Nonviolent, Intimate Terrorism, or Situational Couple Violence. Findings suggest that help-seeking women’s experiences of intimate violence may be diverse, with their roles ranging from victim to perpetrator.